The Role of AI: Speculative Design in Redefining Artistic Collaboration - Chen, Jinghong (Journal of Ecohumanism, 2024)
This paper considers the role of artificial intelligence as an emerging creative collaborator within artistic practices through the frame of speculative design. As technology continues to reshape the creative landscape, AI is increasingly moving from a tool to a co-creative partner in the artistic process. Speculative design is used in this paper to imagine and contrast possible future scenarios in which AI will play a significant role in the creation of art, to explore emerging opportunities and challenges from this integration. The article, guided by three key research questions, investigates how human artists perceive the role of AI in art, the key contributions of AI in collaborative settings, and how speculative design might help clarify the outcomes of AI-assisted versus traditional artistic creation. A comprehensive review of the literature underlines the current state of AI, concerning art forms in visual arts, music, and literature. This, however, must be availed with the gap about research at large in terms of authorship, originality, and ethical implications. The project shows, through speculative scenarios and interviews with practising artists, that while AI holds the potential to extend human creativity through new tools and techniques, several ethical issues regarding authorship and ownership and the possible suppression of human creativity arise. The discussion emphasizes the importance of preserving human agency and the need to develop ethics concerning the use of AI in the arts. In all, while AI affords exciting new opportunities in the realm of collaborative art, great care must be exercised in its integration.